Hubungan Kualitas Tidur dengan Kejadian Anemia pada Remaja Putri di SMK Batik 2 Surakarta - Sahashika, Ailsa Putri; Setiyaningrum, Zulia (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to determine the relationship between sleep quality and the incidence of anemia in adolescent girls at SMK Batik 2 Surakarta. The research was conducted using a cross-sectional design. Samples were selected from 9 classes using Proportional Random Sampling and Simple Random Sampling methods to find research subjects who met the inclusion criteria, namely young women aged 15-19 years and not menstruating. The sample size was determined using the Lameshow formula of 60 young women. Sleep quality data was obtained by filling out the Pittsburgh Sleep Quality Index (PSQI) questionnaire and interviews, the incidence of anemia using the Cyanmethemoglobin method was taken by laboratory staff. To test normality, the Kolmogorov-Smirnov test was used. The research hypothesis was tested using Pearson Product Moment. The results of this study show that there is no correlation between sleep quality and the incidence of anemia, the relationship between these two variables is negative, meaning that the worse the sleep quality, the lower the hemoglobin level value.